Using the SeqCode to validate the names of reclassified lineages of rhizobia and agrobacteria - Melandré van Lill; Emma T. Steenkamp; Marike Palmer; Chrizelle W. Beukes; Stephanus N. Venter (Systematic and Applied Microbiology, 2026)

Argyrolobium legumes from an African centre of endemism associate with novel Bradyrhizobium species harbouring unique sets of symbiosis genes - Mabodiba M. Maake; Chrizelle W. Beukes; Magriet A. van der Nest; Juanita R. Avontuur; Esther K. Muema; Tomasz Stępkowski; Stephanus N. Venter; Emma T. Steenkamp (Molecular Phylogenetics and Evolution, 2026)

Estimated timeline for the evolution of symbiotic nitrogen fixing Paraburkholderia - Lazarus Mavima; Emma T. Steenkamp; Chrizelle W. Beukes; Marike Palmer; Sofie E. De Meyer; Euan K. James; Stephanus N. Venter; Martin P.A. Coetzee (Molecular Phylogenetics and Evolution, 2025)

BISMiS Live: a digital platform for global communication among microbial systematists - Kamlesh Jangid; Wen-Jun Li; Stephanus Venter; Wee Fei Aaron Teo; William Whitman (Systematic and Applied Microbiology, 2025)

Diversity of Environmental Escherichia coli in Subtropical Freshwater Systems of South Africa - Tarren Seale; Volker S. Brözel; Sarah C. Potgieter; Oliver Rupp; Jochen Blom; Emma T. Steenkamp; Stephanus N. Venter (Current Microbiology, 2025)
Escherichia coli is widely used as an indicator of faecal contamination, as it is assumed that faeces from warm-blooded animals is the primary source of E. coli in the environment. However, various studies have shown that E. coli can survive and multiply in environmental niches, including soil, sand and sediment. E. coli can be assigned to eight main phylogroups but environmental E. coli are associated primarily with phylogroups A and B1. In this study, 410 E. coli were isolated from different niches within two peri-urban catchments in the Gauteng province of South Africa. To represent the E. coli circulating within the human population, E. coli was also isolated from sewage before treatment and released into these reservoirs. To capture the diversity of E. coli among these isolates, the β-D-glucuronidase ( uidA ) and mismatch repair ( mutS ) genes were sequenced. While isolates linked to phylogroup B1 dominated as was expected, the recovery of many isolates linked to phylogroup B2, the second most dominant group, was unanticipated. To further investigate this observation, the genomes of representative phylogroup B2 isolates were sequenced and subjected to phylogenetic and functional analyses. The results showed that phylogroup B2 isolates formed a distinct phylogenetic cluster, apparently independent of niche or geographic origin. Our findings also showed that while isolates seem to be associated with environmental samples, they could have the ability to colonize the gut and cause disease as they harboured several virulence factors associated with extraintestinal E. coli .

Mesorhizobium salmacidum sp. nov. and Mesorhizobium argentiipisi sp. nov. are symbionts of the dry-land forage legumes Lessertia diffusa and Calobota sericea - Esther K. Muema; Melandré van Lill; Stephanus N. Venter; Wai Yin Chan; Ricu Claassens; Emma T. Steenkamp (Antonie van Leeuwenhoek, 2025)
Legumes Lessertia diffusa and Calobota sericea , indigenous to South Africa, are commonly used as fodder crops with potential for sustainable livestock pasture production. Rhizobia were isolated from their root nodules grown in their respective soils from the Succulent Karoo biome (SKB) in South Africa, identified and characterized using a polyphasic approach. Sequence analysis of the 16S rRNA gene confirmed all isolates as Mesorhizobium members, which were categorized into two distinct lineages using five housekeeping protein-coding genes. Lineage I included 14 strains from both legumes, while Lineage II comprised a single isolate from C. sericea . Differences in phenotypic traits were observed between the lineages and corroborated by average nucleotide identity analyses. While all strains nodulated their original hosts, strains from C. sericea failed to effectively nodulate L. diffusa and vice versa. Phylogenetic analyses of nitrogen fixation ( nifH ) and nodulation ( nodA , nodC ) loci grouped all strains in a single clade, suggesting that unique symbiotic loci determine nodulation of these legumes. We designated Lineage I and II as Mesorhizobium salmacidum sp. nov. (Ld1326 Ts ; GCA_037179605.1 Ts ) and Mesorhizobium argentiipisi sp. nov. (Cs1330R2N1 Ts ; GCA_037179585.1 Ts ), using genome sequences as nomenclatural types according to the Nomenclatural Code for Prokaryotes using Sequence Data, thus avoiding complications with South Africa's biodiversity regulations. Identifying effective microsymbionts of L. diffusa and C. sericea is essential for conservation of Succulent Karoo Biome, where indigenous invasive species like Vachellia karroo and non-native Australian acacia species are present. Furthermore, targeted management practices using effective symbionts of the studied legumes can sustain the biome's socio-economic contribution through fodder provision.

Options and considerations for validation of prokaryotic names under the SeqCode - Stephanus N. Venter; Luis M. Rodriguez-R; Maria Chuvochina; Marike Palmer; Philip Hugenholtz; Emma T. Steenkamp (Systematic and Applied Microbiology, 2024)

Bacterial community in apparently healthy and asymptomatic Eucalyptus trees and those with symptoms of bacterial wilt - Teresa A. Coutinho; Gabrielle Carstensen; Stephanus N. Venter; ShuaiFei Chen; Marthin Tarigan; Michael J. Wingfield (Journal of Plant Pathology, 2024)
Ralstonia solanacearum and R. pseudosolanacearum are well-known bacterial plant pathogens that cause significant losses to both ornamental and agricultural plants. It has been suggested that they are not the primary cause of bacterial wilt in Eucalyptus species, but rather are opportunistic, taking advantage of trees predisposed to infection by abiotic and biotic factors. To test this hypothesis, the bacterial community within the vascular tissue of asymptomatic Eucalyptus grandis x E. urophylla trees, and those displaying varying stages of infection in China and Indonesia were compared using 16S rRNA profiling. Asymptomatic trees growing in areas where bacterial infections had never previously been reported to occur were included as controls. Ralstonia species were found within the vascular tissue of both asymptomatic and symptomatic trees, in high abundance. In the control samples, bacterial diversity within the vascular tissue was high with a low abundance of Ralstonia species. The presence of Ralstonia species in asymptomatic and control samples supports the hypothesis that these species are latent and/or opportunistic pathogens in E. grandis x E. urophylla trees.

Commentary on the proposed Section 10 amendments to the International Code of Nomenclature of Prokaryotes regarding Candidatus names - William B. Whitman; Stephanus N. Venter (Systematic and Applied Microbiology, 2024)

SeqCode facilitates naming of South African rhizobia left in limbo - Melandré van Lill; Stephanus N. Venter; Esther K. Muema; Marike Palmer; Wai Y. Chan; Chrizelle W. Beukes; Emma T. Steenkamp (Systematic and Applied Microbiology, 2024)

Quis custodiet ipsos custodes? A call for community participation in the governance of the SeqCode - Iain C. Sutcliffe; Luis M. Rodriguez-R; Stephanus N. Venter; William B. Whitman (Systematic and Applied Microbiology, 2024)

Bradyrhizobium xenonodulans sp. nov. isolated from nodules of Australian Acacia species invasive to South Africa - Ricu Claassens; Stephanus N. Venter; Chrizelle W. Beukes; Tomasz Stępkowski; Wai Y. Chan; Emma T. Steenkamp (Systematic and Applied Microbiology, 2023)

Description of two cultivated and two uncultivated new Salinibacter species, one named following the rules of the bacteriological code: Salinibacter grassmerensis sp. nov.; and three named following the rules of the SeqCode: Salinibacter pepae sp. nov., Salinibacter abyssi sp. nov., and Salinibacter pampae sp. nov. - Tomeu Viver; Roth E. Conrad; Marianna Lucio; Mourad Harir; Mercedes Urdiain; Juan F. Gago; Ana Suárez-Suárez; Esteban Bustos-Caparros; Rodrigo Sanchez-Martinez; Eva Mayol; Federico Fassetta; Jinfeng Pang; et al. (Systematic and Applied Microbiology, 2023)

Trinickia dabaoshanensis sp. nov., a new name for a lost species - Paulina Estrada-de los Santos; Marike Palmer; Emma T. Steenkamp; Marta Maluk; Chrizelle Beukes; Ann M. Hirsch; Euan K. James; Stephanus N. Venter (Archives of Microbiology, 2019)

Paraburkholderia strydomiana sp. nov. and Paraburkholderia steynii sp. nov.: rhizobial symbionts of the fynbos legume Hypocalyptus sophoroides - Chrizelle W. Beukes; Emma T. Steenkamp; Elritha van Zyl; Juanita Avontuur; Wai Yin Chan; Ahmed Idris Hassen; Marike Palmer; Lunghile S. Mthombeni; Francina L. Phalane; T. Karabo Sereme; Stephanus N. Venter (Antonie van Leeuwenhoek, 2019)

Biodiversity and ecology of flower-associated actinomycetes in different flowering stages of Protea repens - Zander R. Human; Casparus J. Crous; Francois Roets; Stephanus N. Venter; Michael J. Wingfield; Z. Wilhelm de Beer (Antonie van Leeuwenhoek, 2018)

Practically delineating bacterial species with genealogical concordance - Stephanus N. Venter; Marike Palmer; Chrizelle W. Beukes; Wai-Yin Chan; Giyoon Shin; Elritha van Zyl; Tarren Seale; Teresa A. Coutinho; Emma T. Steenkamp (Antonie van Leeuwenhoek, 2017)

Phylogenomic resolution of the bacterial genus Pantoea and its relationship with Erwinia and Tatumella - Marike Palmer; Emma T. Steenkamp; Martin P. A. Coetzee; Wai-Yin Chan; Elritha van Zyl; Pieter De Maayer; Teresa A. Coutinho; Jochen Blom; Theo H. M. Smits; Brion Duffy; Stephanus N. Venter (Antonie van Leeuwenhoek, 2017)